Off-central acceptor impurity in a spherical quantum dot - Boichuk, V.I.; Leshko, R.Ya.; Bilynskyi, I.V.; Turyanska, L.M. (Condensed Matter Physics, 2012)
The hole energy spectrum with the ion of an acceptor impurity in the quantum dot has been calculated using the spherical approximation of the multiband Luttinger model. The dependence of the hole energy levels on the impurity location in the quantum dot has been studied. The effect of the impurity location on the dipole momentum and the oscillator strength has been analyzed. The hole interlevel absorption coefficient has been calculated.